PERANAN IHSG, SUKU BUNGA, DAN KURS RUPIAH DALAM MEMPENGARUHI PERGERAKAN INFLASI DI INDONESIA - Rahayu, R Maya Putri; Hutajulu, Dinar Melani (PRIMA EKONOMIKA, 2023)
This study aims to analyze the effect of composite index, BI rate, rupiah exchange rate on the inflation in Indonesia. This study was conducted using time series data in the period 1990- 2020. This study utilizes data by Bank of Indonesia, BPS, and BEI. The method used is the Error Correction Model (ECM) which aims to determine the existence in the long term and short term relationships that occur in each variable. The results indicates that exchange rate and BI rate has an effect and is significant on the inflation in the long-term and the short-term. Meanwhile exchange rate on composite index not has a significant on the inflation, both in the short-term and long-term. Keywords: exchange rate; composite index; inflation; interest rates